2015
DOI: 10.1002/berj.3161
|View full text |Cite
|
Sign up to set email alerts
|

A question of quality: do children from disadvantaged backgrounds receive lower quality early childhood education and care?

Abstract: LSE has developed LSE Research Online so that users may access research output of the School. Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Users may download and/or print one copy of any article(s) in LSE Research Online to facilitate their private study or for non-commercial research. You may not engage in further distribution of the material or use it for any profit-making activities or any commercial gain. You may freely distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 13 publications
1
39
0
1
Order By: Relevance
“…Recent research into the universal offer has focused largely on this question of quality, examining disparities between settings and the way this affects children from disadvantaged backgrounds in particular (e.g. Mathers & Smees, ; Gambaro et al ., ). Blanden et al .…”
Section: Introductionmentioning
confidence: 97%
“…Recent research into the universal offer has focused largely on this question of quality, examining disparities between settings and the way this affects children from disadvantaged backgrounds in particular (e.g. Mathers & Smees, ; Gambaro et al ., ). Blanden et al .…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, they have to organise a full‐day service which cannot be covered by the 30 free hours, and the fees for additional hours are growing by a larger rate than their wage (BBC News, ). The research findings that private and voluntary providers are generally of lower quality (Gambaro et al ., ; Melhuish & Gardiner, ) are relevant here, given the middle‐class parents’ reliance on this sector. We argue that full‐time working middle‐class parents are operating in a particular, distinct position in the childcare market, unless they have a more flexible schedule or enough income to combine a nanny with nursery school or a school‐based nursery class.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Raikes et al's (2012) analysis reported 'whether the provider was licensed or accredited' as one of the key criteria used by American parents, while this may not apply to countries where there is a compulsory registration and inspection system, such as in the UK. Surprisingly, although it is now well established from a variety of research that a complex and unequal pattern of childcare use amongst English parents exists (Vincent & Ball, 2001, 2006Vincent et al, 2004Vincent et al, , 2010Gambaro et al, 2015;Speight et al, 2015;Huskinson et al, 2016), there has been little detailed investigation of current parental childcare choosing processes given the unique English childcare market features. For example, the extent to which parents consult Ofsted reports has remained unclear.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In England, only maintained nursery schools and nursery classes (not private providers) must employ qualified teachers. One consequence is that three-and four-year-old children from more disadvantaged areas have access to better qualified staff, as they are more likely than those from richer areas to attend nursery classes (Gambaro et al, 2015). In Germany, the majority of pedagogical staff in childcare centres in Western and Eastern Länder are pre-primary 'educators' (Erzieher/in) (73% and 87%) (Statistisches Bundesamt, 2018a), with a three-year post-secondary vocational qualification (OECD, 2016d).…”
Section: Qualitymentioning
confidence: 99%